Exterior materials for power storage devices

JP7635303B2Active Publication Date: 2025-02-25LISSENOK PACKAGING CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023105973
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-02-25
Estimated Expiration
2036-12-28

AI Technical Summary

Benefits of technology

【0020】 [1]の発明では、保護層が、少なくとも両末端のそれぞれに独立に、水酸基またはカ ルボキシル基を有するポリエステルポリオールと、少なくとも脂肪族系多官能イソシアネ ート化合物を含む多官能イソシアネート硬化剤により形成された数平均分子量が5000 ~50000のポリエステル樹脂を40質量%以上含有する構成であるので、成形性に優 れていて、外装材の表面(保護層の表面)に良好状態に印字できると共に、保護層の表面 は耐溶剤性にも優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635303000004
    Figure 0007635303000004
  • Figure 0007635303000005
    Figure 0007635303000005
  • Figure 0007635303000006
    Figure 0007635303000006
Patent Text Reader

Abstract

To provide an exterior material for a power storage device that has excellent moldability, can ensure good printability on the surface, and also has excellent solvent resistance.SOLUTION: An exterior material for a power storage device includes a base material layer made of heat-resistant resin, a sealant layer as an inner layer, and a metal foil layer placed between the base material layer and the sealant layer, a protective layer is laminated on the surface of the base material layer opposite to the metal foil layer side, the protective layer includes a composition including a polyester resin of 40% by mass or more, formed from a polyester polyol having a number average molecular weight of 5,000 to 50,000 and having at least a hydroxyl group or a carboxyl group independently at each end, and a polyfunctional isocyanate curing agent containing at least an aliphatic polyfunctional isocyanate compound.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to batteries and capacitors used in mobile devices such as smartphones and tablets. Used for hybrid vehicles, electric vehicles, wind power generation, solar power generation, and nighttime electricity storage. An exterior material for an electricity storage device such as a battery or a capacitor, and an electricity storage device exteriorized with said exterior material Regarding s.

[0002] In the claims and the present specification, the term "polyester polyol" is used herein as a The word is, 1) Polyester having hydroxyl groups at both ends of the main chain in the longitudinal direction 2) Polyester having carboxyl groups at both ends of the main chain in the longitudinal direction 3) A polymer having a hydroxyl group at one end of the main chain and a carboxyl group at the other end. Polyester It is used in the sense of including all of the above. [Background technology]

[0003] In recent years, mobile electronic devices such as smartphones and tablet terminals have become thinner and lighter. The lithium-ion secondary batteries, lithium polymer secondary batteries, and lithium-ion batteries that are installed in these vehicles Conventional metals are used as the exterior materials for power storage devices such as on-capacitors and electric double-layer capacitors. Instead of a can, a heat-resistant resin layer (base material layer) / adhesive layer / metal foil layer / adhesive layer / thermoplastic resin layer (See Patent Document 1.) The laminate (exterior material) with the above structure is also used for power sources for automobiles, large power sources for power storage, capacitors, etc. The laminate is also increasingly being fitted with a tensile forming or deep drawing process. By this, the molded product is molded into a three-dimensional shape such as a substantially rectangular parallelepiped shape. This makes it possible to ensure a storage space for storing the main body of the electricity storage device.

[0004] In addition, in order to protect the exterior material and improve formability (slipperiness), a mat is attached to the outside of the base material layer. A configuration in which a varnish layer (protective layer) is provided has also been proposed. For example, cellulose, polyamide, vinyl chloride, modified polyolefin, rubber, acrylic Synthetic resins such as olefins, urethanes, and alkyds, with silica, kaolin, etc. It is described that a matte varnish containing an appropriate amount of inorganic matte agent such as acrylic resin should be used. (See Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2003-288865 A [Patent Document 2] JP 2011-54563 A Summary of the Invention [Problem to be solved by the invention]

[0006] For example, in the case of a battery exterior material, the electrolyte is injected into the main body during the battery manufacturing process. When the electrolyte is injected into the battery, the electrolyte (containing solvent) may adhere to the surface (outer surface) of the exterior material. If the solvent resistance of the outer surface of the exterior material is not good, the appearance of the exterior material will be poor. When the protective layer is made of polyvinyl chloride resin, the molding of the exterior material is good, but the solvent resistance of the exterior surface of the exterior material is poor. is poor (sufficient solvent resistance is not obtained).

[0007] In addition, when a protective layer is formed using fluororesin, the solvent resistance of the exterior material is good. The adhesion of characters and bar codes printed on the exterior surface (outer surface) of the packaging material is insufficient, and the printing Thus, there was a problem of poor printability.

[0008] The present invention has been made in view of the above technical background, and provides a method for producing a molded product having excellent moldability and a surface roughness. This product is an exterior material for power storage devices that has excellent printability and solvent resistance. The present invention aims to provide an outer case for a device and an electricity storage device. [Means for solving the problem]

[0009] In order to achieve the above object, the present invention provides the following means.

[0010] [1] A base layer made of a heat-resistant resin, a sealant layer as an inner layer, and a sealant layer in front of the base layer A metal foil layer disposed between the sealant layers, a protective layer is laminated on a surface of the base layer opposite to the metal foil layer; The protective layer has a hydroxyl group or a carboxyl group at least at each of both ends independently. A polyester polyol having a number average molecular weight of 5,000 to 50,000 and at least A polyfunctional isocyanate curing agent containing an aliphatic polyfunctional isocyanate compound is used. 1. An exterior material for an electricity storage device, comprising 40 mass % or more of a polyester resin.

[0011] [2] The ratio of the number of moles of the polyfunctional aryl group to the total number of moles of the hydroxyl group and the carboxyl group. The equivalent ratio [NCO] / [OH+ 2. An exterior packaging material for an electricity storage device according to item 1 above, wherein the ratio of COOH to total is 0.5 to 5.

[0012] [3] The aliphatic polyfunctional isocyanate compound is a mixture of trimethylolpropane and an aliphatic Adducts of pentaerythritol and aliphatic diisocyanates At least one aliphatic polyfunctional compound selected from the group consisting of adducts with cyanate compounds 3. An exterior material for an electricity storage device according to item 1 or 2 above, which is a functional isocyanate compound.

[0013] [4] The polyester resin constituting the protective layer is the polyester polyol, The polyhydric alcohol formed by the polyfunctional isocyanate curing agent and the trihydric or higher polyhydric alcohol 4. An exterior packaging material for an electricity storage device according to any one of items 1 to 3 above, which is an ester resin.

[0014] [5] The protective layer according to any one of items 1 to 4 above, which contains solid fine particles having an average particle size of 1 μm to 10 μm. The exterior material for an electricity storage device according to any one of claims 1 to 7.

[0015] [6] The electricity storage device according to any one of the above items 1 to 5, wherein the protective layer contains a lubricant. exterior material.

[0016] [7] Any of the above items 1 to 6, wherein a colored layer is disposed between the base layer and the metal foil layer. 2. An exterior material for an electricity storage device according to claim 1.

[0017] [8] The substrate layer and the colored layer are laminated and integrated via an easy-adhesion layer according to the above item 7. Exterior material for the above-mentioned energy storage device.

[0018] [9] A storage battery device comprising a molded article of the exterior material for a storage battery device according to any one of items 1 to 8 above. Exterior case for the device.

[0019]

[10] A main body of an electricity storage device; The packaging material for an electricity storage device according to any one of items 1 to 8 above and / or the packaging material for an electricity storage device according to item 9 above and an exterior member formed of an exterior case for an electronic device, The power storage device is characterized in that the power storage device main body is sheathed with the sheath member. Chair. Effect of the Invention

[0020] In the invention of [1], the protective layer has a hydroxyl group or a carboxyl group at least at both ends independently. A polyester polyol having a carboxyl group and at least an aliphatic polyfunctional isocyanate The number average molecular weight of the polyfunctional isocyanate curing agent containing the isocyanate compound is 5000. Since the composition contains 40% by mass or more of polyester resin with a molecular weight of 0.1 to 50,000, the moldability is excellent. The surface of the exterior material (the surface of the protective layer) can be printed in a good condition, and the surface of the protective layer It also has excellent solvent resistance.

[0021] In the invention of [2], the equivalent ratio [NCO] / [OH+COOH] is in the range of 0.5 to 5. Therefore, the surface of the exterior material (the surface of the protective layer) can be printed in a good condition, and the surface of the protective layer The solvent resistance of the composition can be further improved.

[0022] In the invention of [3], the aliphatic polyfunctional isocyanate compound is the specific aliphatic polyfunctional isocyanate compound. Because it is a polyfunctional isocyanate compound, it maintains a good condition on the surface of the exterior material (surface of the protective layer). This makes it possible to print on the surface of the protective layer and further improve the solvent resistance of the surface of the protective layer.

[0023] In the invention of [4], the polyester resin constituting the protective layer is a polyester polyol, A resin formed from a polyfunctional isocyanate curing agent and a polyhydric alcohol having a valence of 3 or more. Therefore, the crosslink density of the resin is high, and the solvent resistance of the surface of the exterior material (surface of the protective layer) is improved. can be further improved.

[0024] In the invention of [5], the protective layer contains solid fine particles having an average particle size of 1 μm to 10 μm. In this way, the formability of the exterior packaging material can be further improved.

[0025] In the invention of [6], the protective layer contains a lubricant, so that the surface of the exterior material (the surface of the protective layer) is smooth. The flexibility can be improved, and the moldability can be improved.

[0026] In the invention of [7], a colored layer is disposed between a base layer (heat-resistant resin layer) and a metal foil layer. Therefore, the color of the colored layer is visible through the base layer (heat-resistant resin layer), improving the design of the exterior material. In addition, since the colored layer is disposed on the inner side of the base layer, the wearing The color layer will not get scratched or peel off, ensuring durability.

[0027] In the invention of [8], the base layer and the colored layer are laminated and integrated via the easy-adhesion layer, This can sufficiently prevent the colored layer from peeling off from the base layer when the exterior material is molded.

[0028] In the invention of [9], good printability on the surface can be ensured and the ink has excellent solvent resistance. Thus, it is possible to provide an exterior case for an electricity storage device that is molded in a good condition.

[0029] The invention of

[10] ensures good printability on the surface and also has excellent solvent resistance. The battery pack is packaged in a favorable condition with an exterior material for a battery device and / or an exterior case. A device is provided. [Brief description of the drawings]

[0030] [Figure 1] 1 is a cross-sectional view showing one embodiment of an exterior material for an electricity storage device according to the present invention. [Diagram 2] 1 is a cross-sectional view showing one embodiment of an electricity storage device according to the present invention. [Diagram 3] 3 is a perspective view showing an exterior material (flat), an electricity storage device main body, and an exterior case (a molded body molded into a three-dimensional shape) constituting the electricity storage device in FIG. 2 in a separated state before being heat-sealed. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] One embodiment of the exterior material 1 for an electricity storage device according to the present invention is shown in FIG. The device exterior material 1 is preferably used as a packaging material for a lithium ion secondary battery case. However, the present invention is not limited to such applications.

[0032] The packaging material 1 for an electricity storage device has a first adhesive layer (outer The base material layer (heat-resistant resin layer) 2 is laminated and integrated with the metal foil through the adhesive layer 5. A sealant layer (inner adhesive layer) 6 is applied to the other surface (lower surface) of the layer 4 via a second adhesive layer (inner adhesive layer) 6. A protective layer 3 is laminated and integrated on the surface of the base material layer 2 opposite to the metal foil layer 4 side. The layer 7 is integrally laminated (see FIG. 1).

[0033] In this embodiment, an easy-adhesion layer 8 is laminated on the lower surface of the base layer (heat-resistant resin layer) 2. A colored layer 9 is laminated on the lower surface of the adhesive layer 8, and the colored layer 9 and the metal foil layer 4 form a first adhesive layer 5. That is, the metal foil layer 4 and the base material layer (heat resistant In this embodiment, a colored layer 9 is disposed between the base layer ( An adhesive layer 8 is laminated on the lower surface of the heat-resistant resin layer 2 by a gravure coating method, and the adhesive layer 8 The colored layer 9 is laminated on the lower surface of the substrate 1 by printing.

[0034] [Protective layer] In the present invention, the protective layer 7 has at least two independent terminals in the longitudinal direction of the main chain. In particular, a poly(ethylene glycol) having a number average molecular weight of 5,000 to 50,000 and having a hydroxyl group or a carboxyl group is used. A polyfunctional isocyanate composition including an ester polyol and at least an aliphatic polyfunctional isocyanate compound. The composition contains 40% by mass or more of polyester resin formed with a socyanate hardener. Since such a configuration is adopted, the packaging material 1 of the present invention has excellent formability and is easy to use as a packaging material. The surface of the material (the surface of the protective layer 7) can be printed in a good condition, and the surface of the protective layer 7 is resistant to solvents. It is also excellent.

[0035] Examples of the polyester polyol include polyhydric alcohols and polybasic carboxylic acids. A polycondensation reaction is carried out by mixing an acid and carrying out a polycondensation reaction. In order to achieve this, polyester polyols having hydroxyl or carboxyl groups are used. In other words, the polyester polyol is preferably a polyhydric polyol. It is preferably a condensation polymer of an alcohol and a polybasic carboxylic acid. By mixing alcohol and dicarboxylic acid and carrying out a condensation polymerization reaction at 210°C for 20 hours, The "poly(ethylene glycol) having at least one hydroxyl group or one carboxyl group at each of the two terminals independently" The polyhydric alcohol can be produced as an ester polyol. For example, ethylene glycol, diethylene glycol, propylene glycol, , dipropylene glycol, 1,6-hexanediol, neopentyl glycol, 1 ,4-Butylene glycol, Trimethylolpropane, Glycerin, 1,9-Nanone diacetate and 3-methyl-1,5-pentanediol. Examples of the dicarboxylic acid include, but are not limited to, aliphatic dicarboxylic acids, aromatic dicarboxylic acids, and the like. The aliphatic dicarboxylic acid is not particularly limited. Examples of acids that are not commonly used include adipic acid, succinic acid, azelaic acid, suberic acid, and sebacic acid. Examples of the aromatic diacid include cyclic acid, glutaric acid, maleic anhydride, and itaconic anhydride. The carboxylic acid is not particularly limited, but examples thereof include isophthalic acid and terephthalic acid. Acid, naphthalenedicarboxylic acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, Examples of the acid include phthalic anhydride, trimellitic acid, and pyromellitic acid.

[0036] The polyester polyol has a number average molecular weight (Mn) of 5,000 to 50,000. If the number average molecular weight is less than 5000, the solvent resistance is poor. When the solvent adheres to the exterior surface of the exterior material, the surface of the protective layer becomes cloudy and white. On the other hand, if the number average molecular weight exceeds 50,000, the viscosity of the coating solution becomes high. In particular, the polyester polyamide is difficult to apply or has poor coatability. The number average molecular weight of the ol is preferably 8,000 to 40,000, and more preferably 10,000 to 30,000. It is particularly preferable that the range of the molecular weight is 0.000. This can be achieved when the number average molecular weight of the polyester polyol is in the range of 5,000 to 45,000. be.

[0037] The number average molecular weight of the polyester polyol is determined by gel permeation chromatography. The value is calculated as polystyrene equivalent by gel permeation chromatography (GPC). KF805L, KF803L, and KF802 (all manufactured by Showa Denko K.K.) were used. The column temperature was 40°C, tetrahydrofuran (THF) was used as the eluent, and the flow rate was 0.2 mL. / min, detector: differential refractive index (RI) meter, sample concentration 0.02 mass%, molecular weight as standard sample The amount is the number average molecular weight measured using known polystyrene.

[0038] The aliphatic polyfunctional isocyanate compound (curing agent) is not particularly limited. However, for example, hexamethylene diisocyanate (HMDI), tetramethylene diisocyanate (TDMDI), Socyanate, 1,2-propylene diisocyanate, isophorone diisocyanate (I As described above, the aliphatic polyfunctional isocyanate compound is This includes acyclic and cyclic (alicyclic) isocyanates. Also, aliphatic polyfunctional isocyanates Modified compounds of the above aliphatic polyfunctional isocyanate compounds may also be used. The method is not particularly limited, but examples thereof include isocyanuration and polymerization. aliphatic polyfunctional isocyanate compounds obtained by polymerization reactions such as carbodiimide formation Examples of the modified products include dimers of aliphatic polyfunctional isocyanate compounds. , trimers, biurets, allophanates, as well as carbon dioxide and aliphatic polyfunctional isocyanates. A polyisocyanate having a 2,4,6-oxadiazinetrione ring obtained from a monomer of cyanate, etc.

[0039] Among them, the aliphatic polyfunctional isocyanate compound is preferably trimethylolpropane. and aliphatic polyfunctional isocyanate compounds, and pentaerythritol and aliphatic polyfunctional isocyanate compounds At least one selected from the group consisting of adducts with aliphatic polyfunctional isocyanate compounds It is preferable to use aliphatic polyfunctional isocyanate compounds, and more preferably trimethylol. Adducts of diisocyanates and pentaerythritol and aliphatic diisocyanates and an adduct of an aliphatic diisocyanate compound. It is particularly preferable to use one kind of aliphatic polyfunctional isocyanate compound.

[0040] As the curing agent, the aliphatic polyfunctional isomer may be used within a range that does not impair the effects of the present invention. An aromatic polyfunctional isocyanate compound may be used in combination with the isocyanate compound. The aromatic polyfunctional isocyanate compound is not particularly limited, but may be, for example, For example, tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) ), methylene diphenyl diisocyanate, etc.

[0041] The aliphatic polyfunctional isocyanate compound in the polyfunctional isocyanate curing agent The content is preferably set to 30% by mass to 100% by mass, and more preferably 50% by mass to 1 It is more preferable that the content is set to 00% by mass, and furthermore, it is preferable that the content is set to 70% by mass to 100% by mass. It is particularly preferred.

[0042] The polyester resin constituting the protective layer 7 is "the polyester polyol", "The polyfunctional isocyanate curing agent containing the aliphatic polyfunctional isocyanate compound" and and "aliphatic compounds having multiple functional groups in one molecule that can react with isocyanate groups." The aliphatic compound may contain oxygen, nitrogen, The aliphatic compounds include compounds having atoms such as sulfur and chlorine bonded thereto. The aliphatic compound does not contain ster polyol and the polyfunctional isocyanate compound. The molecular weight of the polyester polyol is smaller than the number average molecular weight of the polyester polyol. In this case, the curing reaction proceeds quickly, which has the advantage of improving productivity. When manufacturing exterior materials, a protective layer is first formed on top of the metal foil and sealant film (sealant film). Even if a manufacturing procedure is adopted in which a protective layer is laminated on the surface of the product, the protective layer may adhere to the roll of the processing machine and peel off. In particular, the above-mentioned "Iso The molecular weight of the aliphatic compound having multiple functional groups in one molecule that can react with cyanate groups is 6. It is more preferably in the range of 0 to 9500, and particularly preferably in the range of 100 to 1000. .

[0043] Regarding the aliphatic compound, the functional group capable of reacting with an isocyanate group is not particularly limited. Although not intended to be limiting, examples thereof include a hydroxyl group, an amino group, and a carboxyl group. The above "aliphatic compounds having multiple functional groups in one molecule that can react with isocyanate groups" The specific examples of the alcohol include, but are not limited to, polyhydric alcohols, aliphatic diols, etc. The polyhydric alcohols include amines and dicarboxylic acids. The polyhydric alcohol is an alcohol having two or more hydroxyl groups. There is no particular limitation on the polyhydric alcohol. Examples of such compounds include, but are not limited to, trimethylolethane and trimethylolpropane (TMP). , trimethylolbutane, pentaerythritol, 1,2,6-hexanetriol, Tylpentanediol, Dimethylbutanediol, Ethylene glycol, Glycerin, Ka Among them, trihydric or higher polyhydric alcohols are used. It is preferable.

[0044] The content of the aliphatic compound in the polyester resin is 1% by mass to 30% by mass. It is preferable that the content is 1% by mass to 15% by mass, and more preferable that the content is 3% by mass to A content of 10% by weight is particularly preferred.

[0045] The content of the polyester resin in the protective layer 7 is 40% by mass to 99.9% by mass. In particular, the content of the polyester resin in the protective layer 7 is preferably set to The ratio is more preferably set to 50% by mass to 95% by mass, and more preferably set to 60% by mass to 90% by mass. It is particularly preferable to set it to

[0046] The protective layer 7 preferably further contains solid fine particles. By containing the above, the surface of the packaging material 1 for an electricity storage device (the outer surface of the protective layer 7) has good slip properties. This can further improve the formability of the exterior packaging material for an electricity storage device 1. The gloss value of the surface (outer surface) of the protective layer 7 is set to 30% or less from the viewpoint of improving the slipperiness. It is preferable that the gloss value is set to 1% to 15%. The gloss was measured at a 60° reflection angle using the gloss measuring device "micro-TRI-gloss-s" manufactured by The solid fine particles are not particularly limited, but may be, for example, , silica particles, alumina particles, kaolin particles, calcium oxide particles, calcium carbonate particles Calcium sulfate microparticles, barium sulfate microparticles, calcium silicate microparticles, silica Examples of such beads include ricin resin beads, acrylic resin beads, and fluorine resin beads. Among these, it is preferable to use silica fine particles, barium sulfate fine particles, and acrylic resin beads. As the solid fine particles, it is preferable to use solid fine particles having an average particle size of 1 μm to 10 μm. stomach.

[0047] The content of the solid fine particles in the protective layer 7 is set to 0.1% by mass to 60% by mass. It is preferable that the content is 0.1% by mass or more. When the content is 0.1% by mass or more, the slipperiness during molding can be improved. In addition, by making the content 60 mass % or less, the coating processability during the formation of the protective layer can be improved. In particular, the solid fine particles in the protective layer 7 can be sufficiently secured in shape retention. The content is more preferably set to 5% by mass to 45% by mass, and more preferably set to 10% by mass to 30% by mass. It is particularly preferable to set it to %.

[0048] The protective layer 7 preferably contains a lubricant. This provides excellent slipperiness, and the formability of the exterior material for an electricity storage device 1 can be further improved. The lubricant is not particularly limited, but examples thereof include fatty acid amides, silicones, etc. Examples include wax, polyethylene wax, fluorine-containing polyethylene wax, etc. Can be obtained.

[0049] The protective layer 7 may contain an additive. The additive is not particularly limited. The reaction accelerator may be, for example, a reaction accelerator. For efficiently promoting the reaction between terpolyol and polyfunctional isocyanate compound The reaction accelerator is not particularly limited, but examples thereof include dibutyltin. diacetate, dibutyltin dilaurate, dibutyltin dimaleate, tertiary amines (tribu ethylamine, triethanolamine, etc.

[0050] The thickness of the protective layer 7 (thickness after drying) is preferably set to 1 μm to 10 μm. In order to set the thickness of the protective layer 7 in such a thin range, the protective layer 7 is a coating film (coating film). It is preferable that the coating film is formed by the method described above.

[0051] [Base material layer (heat-resistant resin layer)] The base layer (heat-resistant resin layer) 2 is mainly responsible for ensuring good moldability as an exterior material. In other words, it plays a role in preventing breakage due to necking of the metal foil during molding. The heat-resistant resin constituting the base material layer 2 is a heat-resistant resin that is used when the exterior packaging material 1 is heat-sealed. A heat-resistant resin that does not melt at the sealing temperature is used. A heat-resistant resin having a melting point 10°C or more higher than the melting point of the thermoplastic resin constituting the layer 3 is used. It is preferable to use a heat-resistant resin having a melting point 20° C. or more higher than the melting point of the thermoplastic resin. It is particularly preferred.

[0052] The base layer (heat-resistant resin layer) 2 is a heat-resistant resin stretch film having a hot water shrinkage rate of 2% to 20%. The hot water shrinkage rate is 2% or more, so that the heat resistance of the sheet is improved. The colored layer 9 is sufficiently prevented from peeling off from the heat-resistant resin layer 2 when used in a somewhat severe environment. In addition, the hot water shrinkage rate is 20% or less, so deep drawing and bulging are possible. The colored layer 9 of the exterior material 1 is sufficiently prevented from peeling off from the heat-resistant resin layer 2 when the exterior material 1 is molded by molding or the like. In particular, the heat-resistant resin stretched film has a hot water shrinkage rate of 2.5 to 10 It is preferable to use a heat-resistant resin stretched film having a hot water shrinkage rate of 3.0% to 6. It is more preferable to use a heat-resistant resin stretched film having a hot water shrinkage rate of 3.5 or less. It is particularly preferable to use a heat-resistant resin stretched film having a thickness of 5.0 to 5.0%.

[0053] The "hot water shrinkage rate" is the shrinkage rate of a test piece (10 cm x 10 The dimensions of the test piece in the stretching direction before and after immersion in hot water at 95°C for 30 minutes were This is the modulus of change and is calculated using the following formula:

[0054] Hot water shrinkage rate (%) = {(XY) / X} x 100 X: Dimension in the stretching direction before immersion treatment Y: Dimension in the stretching direction after immersion treatment.

[0055] In addition, when a biaxially stretched film is used, the hot water shrinkage rate is determined in the two stretching directions. The average value of the dimensional change rate is given.

[0056] The hot water shrinkage rate of the heat-resistant resin stretched film can be adjusted, for example, by adjusting the heat setting temperature during stretching. The control can be performed by:

[0057] The heat-resistant resin stretched film 2 is not particularly limited, but may be, for example, a stretched Examples of the stretched film include stretched nylon film, stretched polyamide film, stretched polyester film, etc. Among them, the heat-resistant resin stretched film 2 is preferably a biaxially stretched nylon film. Biaxially oriented polyamide film, biaxially oriented polybutylene terephthalate (PBT) film , biaxially oriented polyethylene terephthalate (PET) film or biaxially oriented polyethylene naphtha It is particularly preferable to use a phthalate (PEN) film. As film 2, a heat-resistant resin biaxially stretched film stretched by simultaneous biaxial stretching method is used. It is preferable to set the "hot water shrinkage in the M direction" to the "hot water shrinkage in the T direction". A heat-resistant resin biaxially stretched film with a shrinkage ratio (MD / TD) in the range of 0.9 to 1.1. It is preferable to use a configuration in which the ratio (MD / TD) is in the range of 0.9 to 1.1. In this case, it is possible to obtain an exterior packaging material 1 having particularly good formability. The "T direction" means the "machine flow direction", and the "T direction" means the "direction perpendicular to the M direction". The nylon is not particularly limited, but for example, 6 nylon Examples of the heat-resistant resin stretched film include nylon, 6,6 nylon, and MXD nylon. The film layer 2 may be formed of a single layer (a single stretched film). Multi-layered structure consisting of stretched polyester film / stretched polyamide film (stretched PET film / It may be formed of a multi-layered material such as a stretched nylon film.

[0058] Among them, the heat-resistant resin stretched film layer 2 is preferably a biaxially stretched polyimide film having a shrinkage rate of 2 to 20%. Amide film, biaxially oriented polyethylene naphthalate (PEN) film with shrinkage rate of 2 to 20% Film or biaxially oriented polyethylene terephthalate (PET) film with a shrinkage rate of 2 to 20% In this case, it is preferable to use a rubber that is suitable for use in molding, sealing, and other somewhat severe environments such as high temperature and humidity. Prevents the colored layer 9 from peeling off from the heat-resistant resin layer 2 when used in an environment where the can be further increased.

[0059] The thickness of the base layer (heat-resistant resin layer) 2 is preferably 12 μm to 50 μm. When a polyester film is used, the thickness is preferably 12 μm to 50 μm. When an iron film is used, the thickness is preferably 15 μm to 50 μm. By setting the value to be equal to or higher than the appropriate lower limit, sufficient strength as an exterior material can be ensured, and By setting the value below the limit, the stress during stretch forming and drawing can be reduced, improving formability. This can be improved.

[0060] [Easy adhesive layer] An easy-adhesion layer 8 is laminated on the inner surface (the surface on the metal foil layer 4 side) of the base material layer (heat-resistant resin layer) 2. The surface of the heat-resistant resin layer 2, which originally has poor adhesiveness, may be coated with a layer having excellent adhesiveness and adhesion. By laminating the adhesive layer 8 by coating with a polar resin or the like, the adhesiveness and adhesion with the colored layer 9 are improved. The adhesiveness can be further improved. The surface to be laminated with the adhesive layer 8 is subjected to a corona treatment or the like in advance to increase wettability. It is preferable.

[0061] The method for forming the easy-adhesion layer 8 is not particularly limited. For example, 2. On the surface of the resin, epoxy resin, urethane resin, acrylic ester resin, methacrylic ester resin, One type selected from the group consisting of steric resins, polyester resins, and polyethyleneimine resins Or, apply an aqueous emulsion (water-based emulsion) of two or more resins and dry it. The adhesive layer 8 can be formed by the above coating method. However, for example, spray coating, gravure roll coating, reverse roll Examples of the coating method include a coating method and a lip coating method.

[0062] The adhesive layer 8 is made of a material selected from the group consisting of epoxy resin, urethane resin, acrylic ester resin, and methacryl resin. The resin is selected from the group consisting of acrylate resin, polyester resin, and polyethyleneimine resin. It is preferable that the composition contains one or more resins such as those mentioned above. By adopting this, the adhesive strength between the heat-resistant resin layer 2 and the colored layer 9 can be further improved. When this exterior material is subjected to deep drawing, stretch forming, etc., the exterior material is sealed. When the heat-resistant resin layer 2 is sealed, the colored layer 9 can be sufficiently prevented from peeling off from the heat-resistant resin layer 2. Even when the exterior material 1 is used in a somewhat harsh environment such as high temperature and humidity, the colored layer 9 has heat resistance. Peeling off from the resin layer 2 can be sufficiently prevented.

[0063] Among them, the easy-adhesion layer 8 contains a urethane resin and an epoxy resin, or In particular, the composition contains a (meth)acrylic ester resin and an epoxy resin. In this case, the adhesive strength between the heat-resistant resin layer 2 and the colored layer 9 can be further improved. This can be done.

[0064] In the case of adopting the former configuration, the urethane resin / epoxy in the adhesive layer 8 The resin content mass ratio is preferably in the range of 98 / 2 to 40 / 60. In this case, the heat resistance The adhesive strength between the reactive resin layer 2 and the colored layer 9 can be further improved. When the urethane resin content ratio becomes greater than the epoxy resin content ratio (98 / 2), This is not preferred because the degree of crosslinking is insufficient, making it difficult to obtain sufficient solvent resistance and adhesive strength. The urethane resin content is higher than the urethane resin / epoxy resin content mass ratio (40 / 60). If the proportion is small, it takes too long to complete the crosslinking, which is undesirable. Among them, the mass ratio of the urethane resin / epoxy resin in the adhesive layer 8 is 90 / 10 to 50 / 10. A range of 0 / 50 is more preferable.

[0065] In the case where the latter configuration is adopted, the (meth)acrylic in the easy-adhesion layer 8 The mass ratio of the acid ester resin to the epoxy resin is preferably in the range of 98 / 2 to 40 / 60. In this case, the adhesive strength between the heat-resistant resin layer 2 and the colored layer 9 can be further improved. The (meth)acrylic ester resin / epoxy resin content ratio is 98 / 2. If the content ratio of (meth)acrylic ester resin becomes too high, the degree of cross-linking becomes insufficient and the durability becomes poor. It is not preferable because it becomes difficult to obtain sufficient solvent resistance and adhesive strength. On the other hand, if the content ratio of the (meth)acrylic acid ester resin is smaller than the content ratio by mass of the (meth)acrylic acid ester resin / epoxy resin (40 / 60), it takes too much time to complete crosslinking, which is not preferable. Among them, it is more preferable that the content ratio by mass of the (meth)acrylic acid ester resin / epoxy resin in the easy-adhesion layer 8 is in the range of 90 / 10 to 50 / 50.

[0066] The resin aqueous emulsion (resin-aqueous emulsion) for forming the easy-adhesion layer 8 ) contains surfactants such as glycols and ethylene oxide adducts of glycols. In this case, a sufficient defoaming effect can be obtained in the resin aqueous emulsion. Therefore, it is possible to form an easily adhesive layer 8 having excellent surface smoothness. It is preferable that the emulsion contains 0.01% by mass to 2.0% by mass.

[0067] In addition, the resin aqueous emulsion (resin-aqueous emulsion) for forming the easy-adhesion layer 8 It is preferable that the dispersion contains inorganic fine particles such as silica and colloidal silica. In this case, a blocking prevention effect can be obtained. It is preferable to add 0.1 to 10 parts by mass per 00 parts by mass.

[0068] The amount of the adhesive layer 8 formed (solid content after drying) is 0.01 g / m 2 ~0.5g / m 2 of It is preferable that the range is 0.01 g / m 2 By the above, the heat-resistant resin stretched film The layer 2 and the colored ink layer 9 can be sufficiently bonded to each other, and the thickness of the adhesive layer is 0.5 g / m 2 Cost is less than This is economical as it can reduce

[0069] The content of the resin in the easy-adhesion layer (after drying) 8 is 88% by mass to 99.9% by mass. It is preferable that:

[0070] [Colored layer] A configuration in which a colored layer 9 is disposed between the base layer 2 and the metal foil layer 4 may be adopted. By adopting such a configuration, it is possible to impart color (including achromatic color) and design to the outer surface of the exterior material 1. It is possible.

[0071] The colored layer 9 is not particularly limited, but may be, for example, a black ink layer, a white ink layer, or the like. Examples of ink layers include a gray ink layer, a red ink layer, a blue ink layer, a green ink layer, and a yellow ink layer. do.

[0072] The black ink layer 9 will now be described. The black ink layer 10 is usually made of carbon black. The composition is formed from a composition comprising:

[0073] Among them, the black ink layer 9 contains carbon black, diamine, polyol and a hardener. It is preferable that the composition contains, but is not limited to, such a composition. .

[0074] In the black ink layer (ink layer after drying) 9, the carbon black content is 15%. The total content of the diamine, polyol and curing agent is 40% by mass to 60% by mass. The content of carbon black is preferably 20% by mass to 85% by mass. It is particularly preferably up to 50% by mass.

[0075] If the carbon black content is less than 15% by mass, the metallic luster of the metal foil layer 4 remains. This can cause the product to lose its solid feel, and it is prone to uneven coloring when molded, so On the other hand, if the carbon black content exceeds 60 mass %, the black ink layer 9 becomes Since the black ink becomes hard and brittle, the adhesive strength to the metal foil layer 4 decreases, and the black ink is easily adhered to the metal foil layer 4 during molding. This is not preferable since it may cause peeling between the ink layer 9 and the ink layer 9 .

[0076] The black ink layer 9 is a total of the carbon black, the diamine and the polyol. It is preferable that the composition contains 2 to 20 parts by mass of the curing agent per 100 parts by mass of the composition. If the amount of the hardener is less than 2 parts by mass, peeling may occur between the metal foil layer 4 and the black ink layer 9 during molding. When the amount of the hardener exceeds 20 parts by mass, the wound exterior material 1 is unwound (rewound). Blocking occurs when the heat-resistant resin layer 2 and the sealant layer (thermoplastic resin layer) 3 are This is undesirable because it is likely to cause problems such as transfer and adhesion to the outer surface of the device.

[0077] The carbon black to be used has an average particle size of 0.2 μm to 5 μm. preferable.

[0078] The diamine is not particularly limited, but examples thereof include ethylenediamine, Dimer diamine, 2-hydroxyethyl ethylenediamine, 2-hydroxyethyl propene Pyrene diamine, dicyclohexylmethane diamine, 2-hydroxyethyl propylene diamine Among them, the diamine includes ethylenediamine, dimer diamine, etc. amine, 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine One or more diamines selected from the group consisting of dicyclohexylmethanediamine and dicyclohexylmethanediamine It is preferred to use amines.

[0079] The diamine reacts with the curing agent (isocyanate, etc.) more quickly than the polyol, and That is, the diamine reacts with the polyol and the curing agent in a time-series reaction. It reacts and promotes crosslinking and curing of the ink composition.

[0080] The polyol is not particularly limited, but may be a polyurethane polyol. a polyol selected from the group consisting of polyester-based polyols and polyether-based polyols; It is preferred to use one or more of these ols.

[0081] The number average molecular weight of the polyol is preferably in the range of 1,000 to 8,000. 000 or more, the adhesive strength after curing can be increased, and By keeping the temperature lower than 100° C., the reaction rate with the curing agent can be increased.

[0082] The curing agent is not particularly limited, but may be, for example, an isocyanate compound. Examples of the isocyanate compound include aromatic, aliphatic, and Various cyclic isocyanate compounds can be used. Diphenylmethane diisocyanate (TDI), Hexamethylene diisocyanate Examples of suitable tertiary esters include isophorone diisocyanate (HDI) and isophorone diisocyanate.

[0083] The colored ink layer (excluding the black ink layer) 9 will be described. The coating layer (excluding the ink layer) is made of polyester resin as the base material and polyfunctional isocyanate as the hardener. A two-component curing polyester urethane resin binder containing an inorganic pigment and a binder compound. It is preferable that the cured film is a cured film of a colored ink composition containing a color pigment.

[0084] The color pigment includes at least an inorganic pigment. In addition to the inorganic pigments, for example, azo pigments, phthalocyanine pigments, condensed polycyclic pigments, The inorganic pigment is not particularly limited, but examples thereof include: For example, carbon black, calcium carbonate, titanium oxide, zinc oxide, iron oxide, aluminum oxide, etc. As the inorganic pigment, those having an average particle size of 0.1 μm to 5 μm are used. It is preferable to use a powder having an average particle size of 0.5 μm to 2.5 μm. It is preferable to disperse the color pigment using a pigment disperser. It is preferable to use a pigment dispersant such as a surfactant when dispersing the color pigment. It is also possible.

[0085] It is preferable that 50% by mass or more of the color pigment is composed of the inorganic pigment. In this case, the hiding power for hiding the metal foil layer 4 is more sufficient, and a sense of dignity and luxury is sufficiently imparted. In particular, the colored ink layer 9 can be formed in a specific color tone. More preferably, the top is composed of said inorganic pigment.

[0086] The thickness of the colored layer 9 (after drying) is preferably 1 μm to 4 μm. By this, the color tone of the colored layer 9 does not remain transparent, and the color and gloss of the metal foil layer 4 are sufficiently maintained. In addition, by making the thickness 4 μm or less, the colored layer 9 does not crack partially during molding. This can be sufficiently prevented.

[0087] The colored layer 9 is not particularly limited, but may be, for example, 1) Ink composition containing carbon black, diamine, polyol, hardener and organic solvent Composition or 2) A polyester resin as the base resin and a polyfunctional isocyanate compound as the hardener. and a color pigment containing an inorganic pigment. Colored ink composition is printed on the surface of the easy-adhesion layer 8 on the lower surface of the heat-resistant resin layer 2 by gravure printing or the like (coating The organic solvent is not particularly limited. Although not essential, examples include toluene.

[0088] The method for forming the colored layer 9 is not particularly limited, but may be, for example, a gravure printing method. , reverse roll coating method, lip roll coating method, etc.

[0089] [Sealant layer (inner layer)] The sealant layer (inner layer) 3 is formed of a thermoplastic resin layer. The inner layer 3 is resistant to highly corrosive electrolytes used in lithium ion secondary batteries, etc. It also has the function of imparting excellent chemical resistance and heat sealability to the exterior packaging material 1. It is something.

[0090] The thermoplastic resin layer 3 is not particularly limited, but may be a thermoplastic resin unstretched film. The thermoplastic resin unstretched film layer 3 is preferably a film layer. However, polyethylene, polypropylene, olefin copolymers, and their acids are not At least one thermoplastic resin selected from the group consisting of modified materials and ionomers. It is preferable that the film is made of an unstretched film.

[0091] Among them, the thermoplastic resin layer 3 contains an elastomer-modified olefin resin. On both sides of the intermediate layer, propylene and other copolymers other than propylene are used as copolymerization components. The random copolymer layer containing the hydroxyl group is laminated on the other random copolymer layers. This is more preferable in that sufficient insulation can be ensured during base sealing.

[0092] The intermediate layer is made of an elastomer-modified olefin resin (polypropylene block copolymer). Polymer) is elastomer modified homopolypropylene or / and elastomer modified lanthanum The elastomer-modified random copolymer is preferably a copolymer. Random polymer containing "propylene" and "other copolymer components other than propylene" as synthetic components It is an elastomer modified rubber copolymer, and the above-mentioned "other copolymer components other than propylene" is not included. Examples of the olefin include, but are not limited to, ethylene, 1-butene, 1-hexene, In addition to olefin components such as 1-pentene and 4-methyl-1-pentene, butadiene etc. are also included. The elastomer is not particularly limited, but may be an olefin-based thermoplastic elastomer. As the olefin-based thermoplastic elastomer, Examples of the rubber include, but are not limited to, EPR (ethylene propylene rubber), Pyrene-butene elastomer, propylene-butene-ethylene elastomer, EPDM ( Ethylene-propylene-diene rubber, among which EPR (ethylene propylene diene rubber) Regarding the elastomer-modified olefin resin, it is preferable to use " The "elastomer modified" may be a product obtained by graft polymerization of an elastomer. The elastomer is an olefin resin (homopolypropylene or / and the random The modified form may be a copolymer of the above-mentioned tertiary amine, or may be other modified forms. stomach.

[0093] The random copolymer (layer) contains "propylene" and "propylene-free" as copolymerization components. The random copolymer is a random copolymer containing "other copolymer components other than the above." The "copolymerization components other than propylene" are not particularly limited, but For example, ethylene, 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene In addition to olefin components such as olefins, butadiene, etc. can be mentioned.

[0094] The thickness of the thermoplastic resin layer 3 is preferably set to 20 μm to 80 μm. By setting the thickness at 80 μm or more, the occurrence of pinholes can be sufficiently prevented. By doing so, the amount of resin used can be reduced, and costs can be reduced. It is particularly preferable that the thickness of the thermoplastic resin layer 3 is set to 30 μm to 50 μm. It may be a single layer or multiple layers.

[0095] [Metal foil layer] The metal foil layer 4 serves to impart a gas barrier property to the packaging material 1, preventing the intrusion of oxygen and moisture. The metal foil layer 4 is not particularly limited, but may be, for example, Examples of the foil include aluminum foil, copper foil, nickel foil, and stainless steel foil. Aluminum foil is the most preferred. Generally, aluminum foil is used as specified in JIS H4160-2006. The thickness of the metal foil layer 4 is preferably 20 μm. It is preferable that the thickness is 20 μm or more. This prevents pinholes from occurring during molding, and the thickness is less than 100μm, making it easy to mold and The stress during drawing can be reduced, improving formability.

[0096] The metal foil layer 4 has at least an inner surface 4a (a surface on the inner adhesive layer 6 side) subjected to a chemical conversion treatment. It is preferable that the container is subjected to such a chemical conversion treatment. It can fully prevent corrosion of the metal foil surface caused by electrolytes in batteries, food, medicines, etc. For example, By carrying out such a treatment, the metal foil is subjected to a chemical conversion treatment. On the surface of the metal foil, 1) An aqueous solution consisting of a mixture of metal salts of phosphoric acid, chromate and fluoride 2) An aqueous solution consisting of a mixture of phosphoric acid, chromic acid, metal fluoride salts, and non-metal fluoride salts. 3) Acrylic resin or / and phenolic resin, phosphoric acid, chromic acid, and gold fluoride Aqueous solutions of metal salts The chemical conversion treatment is carried out by coating the surface with any one of the above and then drying it.

[0097] [Outer adhesive layer (first adhesive layer)] The outer adhesive layer 5 is not particularly limited, but may be, for example, a two-component curing adhesive. The two-component curing adhesive may include, for example, an adhesive layer formed by a two-component curing adhesive. Although not limited to these, examples of the adhesive include two-component curing urethane adhesives, two-component curing polyester adhesives, etc. The two-component curing urethane adhesives include, but are not limited to, Although not limited thereto, for example, it does not contain a polyol component and an isocyanate component. Examples of the two-component curing urethane adhesive include a two-component curing urethane adhesive. It is particularly suitable for use in bonding by a dry lamination method. Examples of the polyol include, but are not limited to, polyester polyol, polyether polyol, etc. The isocyanate component is not particularly limited, but For example, TDI (tolylene diisocyanate), HMDI (hexamethylene diisocyanate) diisocyanate), MDI (methylenebis(4,1-phenylene)diisocyanate), etc. The thickness of the outer adhesive layer 5 is set to 2 μm to 5 μm. It is preferable that the thickness is set to 3 μm to 4 μm. The adhesive layer 5 contains an inorganic or organic anti-blocking agent and an amide slip agent. It may be added.

[0098] The outer adhesive layer 5 is, for example, an adhesive such as the two-component curing adhesive, which is 4” or / and “the lower surface of the heat-resistant resin layer 2” via an easy-adhesion layer 8 The lower surface of the colored layer 9 is coated with the colored layer 9 by a method such as gravure coating. The above-mentioned method for forming the outer adhesive layer 5 is merely an example, and it is not intended to be limited to such a form. The present invention is not limited to the synthesis method.

[0099] [Inner adhesive layer (second adhesive layer)] The inner adhesive layer 6 is an inner adhesive layer 5 that bonds the metal foil layer 4 and the sealant layer 3. In order to prevent deterioration of the laminate strength over time due to the influence of electrolyte, etc., at least metal foil layer 4 The adhesive resin used has good adhesive properties to both the adhesive layer 2 and the sealant layer 3. The specific type of resin is not particularly limited, but for example, maleic acid dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and mesaconic acid; Dicarboxylic anhydrides such as malonic acid, itaconic anhydride, and mesaconic anhydride, acrylic acid, methacryloyl Carboxylic acid, crotonic acid, itaconic acid, and other carboxyl group-containing monomers are added to polypropylene. Among these, maleic anhydride resins are preferred. It is preferable to use a resin which has been graft-modified with polyaniline, acrylic acid or methacrylic acid. In particular, maleic anhydride modified polyolefin resins are preferred. Although there is no particular limitation, for example, polypropylene is dissolved in an organic solvent. This is reacted with an acid (maleic anhydride, etc.) in the presence of a radical generator. Propylene is heated and melted, and reacted with an acid (maleic anhydride, etc.) in the presence of a radical generator. Examples of the method include a melting method in which the mixture is reacted with the solvent.

[0100] In addition, the inner adhesive layer 6 ensures sufficient resistance to electrolyte, thereby increasing the service life of the exterior material. From the viewpoint of achieving this, polyolefin resin having a carboxyl group in its chemical structure and multifunctional isomer It is particularly preferable that the adhesive composition comprises an adhesive agent containing a socyanate compound. The inner adhesive layer 6 is made of, for example, a polyolefin resin having a carboxyl group and a polyfunctional An adhesive liquid containing an isocyanate compound and an organic solvent is applied to the metal foil layer 4 and / or The adhesive layer 2 can be formed by applying the adhesive to the sealant layer 3 and drying the applied adhesive.

[0101] The polyolefin resin having a carboxyl group (hereinafter referred to as "carboxyl group-containing polyolefin resin") The polyolefin resin (sometimes called "olefin resin") is not particularly limited, but examples thereof include: Modified polyolefin by graft polymerization of ethylenically unsaturated carboxylic acid or its acid anhydride. and copolymer resins of olefin monomers and ethylenically unsaturated carboxylic acids. The polyolefin is not particularly limited, but examples thereof include For example, homopolymers of olefin monomers such as ethylene, propylene, butene, etc., or copolymers of these olefins. Examples of the ethylenically unsaturated carboxylic acid include copolymers of fin monomers and the like. Although not particularly limited, examples thereof include acrylic acid, methacrylic acid, maleic acid, and furan. These ethylenically unsaturated carboxylic acids include, for example, ethylenic acid, crotonic acid, and itaconic acid. Only one type may be used, or two or more types may be used in combination. As the polyolefin resin, one that dissolves in an organic solvent is preferably used.

[0102] Among them, the carboxyl group-containing polyolefin resin is a propylene homopolymer. The copolymer of propylene and ethylene is added with an ethylenically unsaturated carboxylic acid or its acid free acid. It is preferable to use a modified polyolefin resin obtained by graft polymerization of water. The carboxyl group-containing polyolefin resin may be of a single composition or of two compositions having different melting points. A mixture of more than one type may also be used.

[0103] The polyfunctional isocyanate compound reacts with the carboxyl group-containing polyolefin resin. In response to this, it acts as a curing agent that cures the adhesive composition. The anate compound is not particularly limited, but for example, tolylene diisocyanate Diphenylmethane diisocyanate, Hexamethylene diisocyanate, Isophorone lon diisocyanate or isocyanurate modified products of these diisocyanate compounds, Biuret modified products, or the above diisocyanate compounds are mixed with various solvents such as trimethylolpropane. and the like. The polyfunctional isocyanate may be used alone or in combination of two or more. As the isocyanate compound, a polyfunctional isocyanate compound that dissolves in an organic solvent is preferably used. can be done.

[0104] The organic solvent is capable of dissolving the carboxyl group-containing polyolefin resin or There is no particular limitation as long as the material can be dispersed. An organic solvent capable of dissolving the silyl group-containing polyolefin resin is preferably used. The organic solvent is evaporated from the adhesive liquid by heating or the like. The organic solvent which can be easily removed is preferably used. The fin resin can be dissolved and easily removed by volatilization by heating or the like. The organic solvent is not particularly limited, but examples thereof include aromatic solvents such as toluene and xylene. Aromatic organic solvents, aliphatic organic solvents such as n-hexane, cyclohexane, methylcyclohexane Alicyclic organic solvents such as methyl ethyl ketone (MCH), ketone organic solvents such as methyl ethyl ketone (MEK) These organic solvents may be used alone or in combination of two or more. is also good.

[0105] In the adhesive liquid or the adhesive resin composition, a carboxyl group-containing polyolefin resin The isocyanate of the polyfunctional isocyanate compound isothiocyanate to the hydroxyl group constituting the carboxyl group of the The equivalent ratio of socyanate groups [NCO] / [OH] is preferably set to 0.5 to 10.0. If the content is set within such a range, the adhesive composition will have excellent initial adhesive performance. At the same time, the adhesive strength between the metal foil layer 4 and the sealant layer 3 due to the electrolyte of the battery can be improved. This effectively suppresses the deterioration of electrolyte over a long period of time, and further improves electrolyte resistance. The equivalent ratio [NCO] / [OH] is set to 1.0 to 9.0. It is more preferable that the ratio is set to 1.0 to 6.0.

[0106] If necessary, a reaction accelerator, a tackifier, a plasticizer, etc. may be added to the adhesive liquid or the adhesive composition. Additives such as the above may also be contained.

[0107] The thickness of the inner adhesive layer 6 is preferably set to 1 μm to 10 μm. By having a thickness of 10μm or less, sufficient adhesive strength can be obtained, and by having a thickness of 10μm or less, the adhesive strength can be increased by 10μm or less. The air barrier properties can also be improved.

[0108] In the above embodiment, the easy-adhesion layer 8, the colored layer 9, the first adhesive layer 5, and the second adhesive layer 6 are However, none of these layers are essential components, and It is also possible to adopt a configuration in which no such function is provided.

[0109] By forming (deep drawing, stretch forming, etc.) the exterior material 1 for an electricity storage device of the present invention, In this way, an outer case 10 for an electricity storage device can be obtained (see FIG. 3). The dressing material 1 can also be used as it is without being subjected to molding (see FIG. 3).

[0110] One embodiment of an electricity storage device 30 constructed using the exterior material 1 of the present invention is shown in FIG. The power storage device 30 is a lithium ion secondary battery. As shown in FIG. 1, the exterior case 10 obtained by molding the exterior material 1 and the flat surface that was not used for molding are The exterior material 1 constitutes an exterior member 15. In the storage recess of the exterior case 10 obtained by forming the outer case 10, a substantially rectangular parallelepiped-shaped electricity storage device main body ( A gas-chemical element (31) is housed in the storage device body 31, and the exterior material 1 of the present invention is placed on the storage device body 31. The inner layer 3 is placed on the inner side (lower side) without being molded, and the flat exterior material 1 The periphery of the inner layer 3 and the inner layer 3 of the flange portion (sealing periphery) 29 of the outer case 10 The above components are sealed by heat sealing to form the electricity storage device of the present invention. The housing recess of the outer case 10 is provided with a space 30 (see FIGS. 2 and 3). The surface of the recess is an inner layer (sealant layer) 3, and the outer surface of the recess is a protective layer 7. (See Figure 3.)

[0111] In FIG. 2, 39 denotes a portion between the peripheral edge of the exterior material 1 and the flange portion of the exterior case 10 ( The sealing edge 29 is a heat-sealed portion joined (fused) to the storage device. In the seat 30, the tip of the tab lead connected to the electricity storage device main body 31 is Although it is led out to the outside of the material 15, it is not shown in the figure.

[0112] The electric storage device main body 31 is not particularly limited, but may be, for example, a battery. Examples of the body portion include a main body portion, a capacitor body portion, and a condenser body portion.

[0113] The width of the heat-sealed portion 39 is preferably set to 0.5 mm or more. By setting the width of the heat seal portion 39 to the width or more, the sealing can be performed reliably. It is preferable to set it to 3 mm to 15 mm.

[0114] In the above embodiment, the exterior member 15 includes an exterior case 10 obtained by molding the exterior material 1, The structure was made up of a flat exterior material 1 (see Figures 2 and 3), but this type of combination For example, the exterior member 15 may be configured to include a pair of exterior members 1. Alternatively, the housing 10 may be configured as a pair of exterior cases 10. EXAMPLES

[0115] Next, specific examples of the present invention will be described, but the present invention is not limited to these examples. Not limited to this.

[0116] <Example 1> 50 parts by mass of carbon black with an average particle size of 0.8 μm, 5 parts by mass of ethylenediamine, 45 parts by mass of ester-based polyol (number average molecular weight: 2500) was added to obtain the base material. 100 parts by mass of the base material is mixed with 3 parts by mass of tolylene diisocyanate (TDI) as a curing agent. Then, 50 parts by mass of toluene was added and thoroughly stirred to prepare the ink. A composition was obtained.

[0117] In addition, Mitsui Chemicals' "Takelac W-6010" 70% water-based urethane resin was used. Water-based epoxy resin "Denacol EX-521" manufactured by Nagase Chemtec Corporation 30 parts by weight of colloidal silica "S" manufactured by Nissan Chemical Industries, Ltd. as an anti-blocking agent. Mix 5 parts by mass of Notex ST-C (average particle size 10 nm to 20 nm) and then ionize. The adhesive composition for forming an easy-adhesion layer having a non-volatile content of 2% by mass was obtained by diluting the mixture with ethyl alcohol and water. Got it.

[0118] Next, the biaxial stretched film was stretched by simultaneous biaxial stretching to obtain a thickness of 15 μm and a hot water shrinkage rate of 4.0%. Stretched nylon (6 nylon) film (heat-resistant resin stretched film layer, MD / TD=0.9 5) The adhesive composition for forming an easy-adhesion layer is applied to one surface of 2 by a gravure roll coating method. After applying and drying, leave it in a 40℃ environment for one day to allow the hardening reaction to proceed. Formation amount 0.1g / m 2 Thus, an easy-adhesion layer 8 was formed.

[0119] Next, the ink composition is applied to the surface of the adhesive layer 8 of the biaxially oriented nylon film 2. After printing (coating) using the rabia printing method, leave it in a 40℃ environment for one day. The crosslinking reaction proceeds while drying, forming a colored layer (black ink layer) 9 having a thickness of 3 μm. A first laminate was obtained.

[0120] Furthermore, on the biaxially oriented nylon film 2 of the first laminate (on the unlaminated surface), 55 parts by mass of polyester (number average molecular weight: 5300) having hydroxyl groups at both ends in the length direction, Adduct of trimethylolpropane and hexamethylene diisocyanate (referred to as "A" in the table) Duct body A) 13 parts by mass, powdered silica with an average particle size of 2 μm, 2 parts by mass, 20 parts by mass of 2 μm barium sulfate, 5 parts by mass of acrylic resin beads with an average particle size of 7 μm, 5 parts by mass of polyethylene wax and 100 parts by mass of solvent (50 parts by mass of methyl ethyl ketone: After applying a protective layer-forming composition consisting of 50 parts by mass of toluene, the composition was left in a 60°C environment for 3 days. The reaction is allowed to proceed by leaving the material to form a protective layer 7 having a thickness of 2 μm, forming a second laminate. In the protective layer forming composition, the equivalent ratio [NCO] / [OH+COOH] was 2.9.

[0121] On the other hand, polyacrylic acid, phosphoric acid, trivalent chromium, and the like are applied to both sides of an aluminum foil 4 having a thickness of 35 μm. A chemical conversion treatment solution consisting of a chromium compound, water, and alcohol is applied to the surface, and the surface is dried at 180°C. The amount of adhesion is 5mg / m 2 It was made so that:

[0122] Next, a polyester polyurethane film is applied to one side of the aluminum foil 4 that has been subjected to the chemical conversion treatment. The second laminate is attached to the colored layer (black ink layer) 9 side via an adhesive 5, and then On the other side of the aluminum foil 4, a thick maleic anhydride-modified polypropylene adhesive 6 is applied. After laminating an unstretched polypropylene film (thermoplastic resin layer) 3 having a thickness of 30 μm, The product was left to stand in a 0° C. environment for 5 days, thereby obtaining an outer casing material 1 for an electricity storage device shown in FIG.

[0123] <Example 2> In the composition for forming a protective layer, "a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain" is used. 55 parts by weight of ester (number average molecular weight: 5300), trimethylolpropane and hexamethylene "13 parts by mass of an adduct with diisocyanate" and "13 parts by mass of an adduct with hydroxyl groups at both ends of the main chain in the longitudinal direction" 63 parts by mass of polyester (number average molecular weight: 9800), trimethylolpropane and 5 parts by mass of hexamethylene diisocyanate adduct, and the equivalent ratio [NCO] The same procedure as in Example 1 was repeated except that a protective layer-forming composition having a ratio of / [OH+COOH] of 1.8 was used. As a result, an exterior material 1 for an electricity storage device shown in FIG. 1 was obtained.

[0124] <Example 3> The protective layer-forming composition of Example 2 was further mixed with erucic acid amide at a concentration of 5000 ppm. The procedure of Example 2 was repeated except that the composition for forming the protective layer was used. Thus, an exterior material 1 for an electricity storage device shown in FIG. 1 was obtained.

[0125] <Example 4> In the composition for forming a protective layer, "a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain" is used. 55 parts by mass of trimethylolpropane and hexamethylene diamine (number average molecular weight: 5300), 13 parts by mass of adduct with isocyanate" and "having hydroxyl groups at both ends in the longitudinal direction of the main chain" 65 parts by weight of polyester (number average molecular weight: 14500), trimethylolpropane and hexane The equivalent ratio [NCO] / The same procedure as in Example 1 was repeated except that a protective layer-forming composition having an [OH+COOH] of 1.6 was used. Thus, an exterior material 1 for an electricity storage device shown in FIG. 1 was obtained.

[0126] <Example 5> In the composition for forming the protective layer, "trimethylolpropane and hexamethylene diisocyanate "3 parts by mass of adduct with trimethylolpropane and hexamethylene diisocyanate" 1.5 parts by mass of an adduct with an anate and trimethylolpropane and tolylene diisocyanate The same as in Example 4, except that the amount was changed to "1.5 parts by mass of an adduct with anate (TDI)". As a result, an exterior material 1 for an electricity storage device shown in FIG. 1 was obtained.

[0127] <Example 6> In the composition for forming a protective layer, "a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain" is used. 55 parts by mass of trimethylolpropane and hexamethylene diamine (number average molecular weight: 5300), 13 parts by mass of adduct with isocyanate" and "having hydroxyl groups at both ends in the longitudinal direction of the main chain" 65 parts by weight of polyester (number average molecular weight: 14,500), pentaerythritol and hexaerythritol Adduct with samethylene diisocyanate: 3 parts by mass; equivalent ratio [NCO] / [ The same procedure as in Example 1 was repeated except that a protective layer-forming composition having a [OH+COOH] of 1.7 was used. Thus, an exterior material 1 for an electricity storage device shown in FIG. 1 was obtained.

[0128] <Example 7> Polyester with hydroxyl groups at both ends of the main chain (number average molecular weight: 14,500) Instead, a polyester having hydroxyl groups at both ends of the main chain (number average molecular weight: 19 The exterior material for an electricity storage device 1 shown in FIG. 1 was prepared in the same manner as in Example 4, except that 600) was used. Got it.

[0129] <Example 8> Polyester with hydroxyl groups at both ends of the main chain (number average molecular weight: 14,500) Instead, a polyester having hydroxyl groups at both ends of the main chain (number average molecular weight: 28 The exterior material for an electricity storage device 1 shown in FIG. 1 was prepared in the same manner as in Example 4, except that 500) was used. Got it.

[0130] <Example 9> Polyester (number average molecular weight: 5300) with hydroxyl groups at both ends of the main chain Instead, a polyester having hydroxyl groups at both ends of the main chain (number average molecular weight: 490 00) was used, the same procedure as in Example 1 was repeated to obtain an exterior material for an electricity storage device 1 shown in FIG. Ta.

[0131] <Example 10> Polyester (number average molecular weight: 9800) with hydroxyl groups at both ends of the main chain Instead, a polyester having carboxyl groups at both ends of the main chain in the longitudinal direction (number average molecular weight The exterior material for an electricity storage device shown in FIG. 1 was prepared in the same manner as in Example 3, except that a cellulose acetate ester resin (C100: 9800) was used. I got 1.

[0132] <Example 11> As a composition for forming a protective layer, a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain ( Number average molecular weight: 9800) 57 parts by weight, trimethylolpropane and hexamethylene diisopropyl 10 parts by mass of adduct with cyanate, 1 part by mass of trimethylolpropane (polyhydric alcohol) 2 parts by weight of powdered silica having an average particle size of 2 μm, 20 parts by weight of barium sulfate having an average particle size of 2 μm The electrical storage device exterior material 1 shown in FIG. 1 was prepared in the same manner as in Example 2, except that a protective layer-forming composition consisting of 5 parts by mass of acrylic resin beads having an average particle size of 7 μm and 5 parts by mass of wax was used. obtained.

[0133] <Example 12> As a composition for forming a protective layer, a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain ( Number average molecular weight: 9800) 57 parts by weight, trimethylolpropane and hexamethylene diisopropyl 10 parts by mass of adduct with cyanate, 1 part by mass of pentaerythritol (polyhydric alcohol) 2 parts by mass of powdered silica having an average particle size of 2 μm; 20 parts by mass of barium sulfate having an average particle size of 2 μm; Formation of a protective layer consisting of 5 parts by weight of acrylic resin beads with an average particle size of 7 μm and 5 parts by weight of wax The electrical storage device exterior material 1 shown in FIG. 1 was prepared in the same manner as in Example 2, except that the composition for use was used. Got it.

[0134] <Example 13> As a composition for forming a protective layer, a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain ( Number average molecular weight: 9800) 57 parts by weight, trimethylolpropane and hexamethylene diisopropyl 10 parts by weight of cyanate adduct, 1 part by weight of glycerin (polyhydric alcohol), average particle size 2 parts by weight of powdered silica with a diameter of 2 μm, 20 parts by weight of barium sulfate with an average particle size of 2 μm, and an average particle size of 7 A composition for forming a protective layer, which is composed of 5 parts by mass of acrylic resin beads of 1 μm and 5 parts by mass of wax, Except for using the above, the same procedure as in Example 2 was carried out to obtain an outer casing material for an electricity storage device 1 shown in FIG.

[0135] <Example 14> In the composition for forming a protective layer, "a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain" is used. 55 parts by mass of trimethylolpropane and hexamethylene diamine (number average molecular weight: 5300), "13 parts by mass of adduct with isocyanate" and "13 parts by mass of hydroxyl groups at both ends of the main chain It has four hydroxyl groups (hydroxyl groups at both ends of the main chain in the longitudinal direction and 65 parts by weight of polyester (number average molecular weight: 14200) having two hydroxyl groups at each position, 3 parts by mass of an adduct of dimethylolpropane and hexamethylene diisocyanate Furthermore, the following protective layer-forming composition having an equivalent ratio [NCO] / [OH+COOH] of 0.8 was used. Other than that, the same procedures as in Example 1 were carried out to obtain an outer casing material for an electricity storage device 1 shown in FIG.

[0136] <Example 15> In the composition for forming a protective layer, "a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain" is used. 55 parts by mass of trimethylolpropane and hexamethylene diamine (number average molecular weight: 5300), "13 parts by mass of adduct with isocyanate" and "13 parts by mass of hydroxyl groups at both ends of the main chain It has four hydroxyl groups (hydroxyl groups at both ends of the main chain in the longitudinal direction and 65 parts by weight of polyester (number average molecular weight: 11200) having two hydroxyl groups at each position, 3 parts by mass of an adduct of dimethylolpropane and hexamethylene diisocyanate Furthermore, the following protective layer-forming composition having an equivalent ratio [NCO] / [OH+COOH] of 0.9 was used. Other than that, the same procedures as in Example 1 were carried out to obtain an outer casing material for an electricity storage device 1 shown in FIG.

[0137] <Comparative Example 1> As a composition for forming a protective layer, 65% of fluorine-containing polyol (number average molecular weight: 15,000) was used. parts by mass, adduct of trimethylolpropane and hexamethylene diisocyanate 3 parts by mass 2 parts by weight of powdered silica having an average particle size of 2 μm, 20 parts by weight of barium sulfate having an average particle size of 2 μm A protective layer consisting of 5 parts by mass of acrylic resin beads having an average particle size of 7 μm and 5 parts by mass of wax The electrical storage device exterior material 1 shown in FIG. 1 was produced in the same manner as in Example 1, except that the composition was used. obtained.

[0138] <Comparative Example 2> As a composition for forming a protective layer, 53% polyurethane polyol (number average molecular weight: 5400) was used. parts by weight, 15 parts by weight of an adduct of trimethylolpropane and hexamethylene diisocyanate parts by weight, 2 parts by weight of powdered silica with an average particle size of 2 μm, 20 parts by weight of barium sulfate with an average particle size of 2 μm a protective layer consisting of 5 parts by mass of acrylic resin beads having an average particle size of 7 μm and 5 parts by mass of wax The exterior material for a power storage device shown in FIG. 1 was produced in the same manner as in Example 1, except that the forming composition was used. I got 1.

[0139] <Comparative Example 3> As a composition for forming a protective layer, 53% of acrylic polyol (number average molecular weight: 3400) was used. 15 parts by mass of adduct of trimethylolpropane and hexamethylene diisocyanate 2 parts by weight of powdered silica having an average particle size of 2 μm, 20 parts by weight of barium sulfate having an average particle size of 2 μm A protective layer consisting of 5 parts by mass of acrylic resin beads having an average particle size of 7 μm and 5 parts by mass of wax The electrical storage device exterior material 1 shown in FIG. 1 was produced in the same manner as in Example 1, except that the composition was used. obtained.

[0140] <Comparative Example 4> In the composition for forming a protective layer, "a polyester having hydroxyl groups at both ends in the longitudinal direction of the main chain" is used. 55 parts by mass of trimethylolpropane and hexamethylene diamine (number average molecular weight: 5300), 13 parts by mass of adduct with isocyanate" and "having hydroxyl groups at both ends in the longitudinal direction of the main chain" 53 parts by weight of polyester (number average molecular weight: 3900), pentaerythritol and hexaerythritol 15 parts by mass of adduct with methylene diisocyanate" and the equivalent ratio [NCO] / [ The same procedure as in Example 1 was repeated except that a protective layer-forming composition having a [OH+COOH] of 2.6 was used. Thus, an exterior material 1 for an electricity storage device shown in FIG. 1 was obtained.

[0141] <Comparative Example 5> In the composition for forming the protective layer, "trimethylolpropane and hexamethylene diisocyanate "13 parts by mass of adduct with trimethylolpropane and tolylene diisocyanate" The same procedure as in Example 1 was repeated except that the amount of the adduct with TDI was changed to 13 parts by mass. An exterior material 1 for an electricity storage device shown in FIG. 1 was obtained.

[0142] In the table, trimethylolpropane and hexamethylene diisocyanate (H The adduct with pentaerythritol and hexamethasone is referred to as "adduct A." The adduct with ethylene diisocyanate (HMDI) is referred to as "adduct B" and The adduct of methylolpropane and tolylene diisocyanate (TDI) is called "adduct It was written as "Body C".

[0143] [Table 1]

[0144] [Table 2]

[0145] [Table 3]

[0146] The exterior materials for electricity storage devices obtained as described above were evaluated based on the following evaluation methods. The results are shown in Tables 1 to 3.

[0147] <Moldability evaluation method> A storage device was manufactured using an Amada Corporation stretch molding machine (product number: TP-25C-X2). The exterior material for the building is molded into a rectangular shape of 55 mm long x 35 mm wide x 8 mm deep. The moldability was evaluated based on the following criteria. (Judgment criteria) "◎": No pinholes or cracks were observed. "◯": No pinholes or cracks, but slight cloudiness is observed in the protective layer. "△": A few pinholes were generated in a very small area, but practically none were generated. "X": Pinholes and cracks occurred in the corners.

[0148] <Printability evaluation method> A white ink was applied to the surface (outer surface) of the protective layer of each exterior material using an inkjet printer. A barcode (dot size: diameter 0.25 mm) was printed using ink. - Check whether the barcode can be read by a barcode reader without any problems, and whether the printed barcode The printability was evaluated based on the following criteria from the viewpoint of whether or not bleeding occurred. (Judgment criteria) "◎": The barcode could be read without any problems using a barcode reader. There was no bleeding. "○": The barcode can be read without any problems using a barcode reader. There is a slight blur, but it is not a problem. "△": Some bleeding is observed, but the barcode can be read without any problems using a barcode reader. "X": The barcode could not be read by the barcode reader. There was a large amount of bleeding.

[0149] <Solvent resistance evaluation method (ethanol)> Each exterior material was cut into a test piece measuring 10 cm in length and 10 cm in width, and the protection of the test piece was After dropping 1 mL (1 cc) of ethanol onto the surface (outer surface) of the layer, The test piece was rubbed 10 times with a sliding member with cotton wrapped around the surface of a 1 g weight. After 10 strokes, the appearance of the surface (outer surface) of the protective layer of the test piece was visually inspected and judged as follows: Solvent resistance (ethanol) was evaluated based on the criteria. (Judgment criteria) "◎": There was no change in appearance even after 10 round trips. "○": There was no change in appearance from the 1st to the 7th round trips, but a change in appearance occurred after the 8th round trip. "△": There was no change in appearance from the first to fourth round trips, but a change in appearance occurred after the fifth round trip. "X": Appearance changed after one stroke (poor solvent resistance).

[0150] <Solvent resistance evaluation method (methyl ethyl ketone)> Except that 1 mL of methyl ethyl ketone (MEK) was used instead of 1 mL of ethanol. Solvent resistance (methyl ethyl ketone) was evaluated in the same manner as the above solvent resistance evaluation method (ethanol). The evaluation criteria were the same as those for the solvent resistance evaluation method (ethanol). It is.

[0151] As is clear from the table, the exterior packaging materials for electricity storage devices of Examples 1 to 15 of the present invention have excellent moldability. The printability was excellent, and the solvent resistance was also excellent.

[0152] In contrast, Comparative Examples 1 to 5, which deviate from the range specified by the present invention, had the following problems: That is, the printability was poor in the packaging material of Comparative Example 1. In addition, in the packaging materials of Comparative Examples 2 to 5, The solvent resistance to MEK was extremely poor. [Industrial Applicability]

[0153] The exterior material for an electricity storage device according to the present invention and the exterior case for an electricity storage device according to the present invention are, As a specific example, - Energy storage devices such as lithium secondary batteries (lithium ion batteries, lithium polymer batteries, etc.) Lithium-ion capacitor Electric double layer capacitor ·All-solid-state battery The battery pack according to the present invention can be used as an exterior material or an exterior case for various types of battery devices. Examples of the device include the various types of electricity storage devices exemplified above. [Explanation of symbols]

[0154] 1. Exterior materials for power storage devices 2...Base material layer 3...Sealant layer (inner layer) 4…Metal foil layer 5...First adhesive layer (outer adhesive layer) 6...Second adhesive layer (inner adhesive layer) 7…Protective layer 8…Easy adhesion layer 9…Colored layer 10...Outer case for power storage device (molded body) 15…Exterior material 30…Electricity storage device 31...Electricity storage device main body

Claims

1. The device includes an exterior member and a main body of the power storage device. the exterior member includes a base layer made of a heat-resistant resin, a sealant layer as an inner layer, and a metal foil layer disposed between the base layer and the sealant layer, The electricity storage device is characterized in that a protective layer is provided on the surface of the base material layer opposite to the metal foil layer, the protective layer containing 40 mass% or more of a polyester resin formed from a polyester polyol having a number average molecular weight of 5,000 to 50,000 and having a hydroxyl group or a carboxyl group, independently at least at both ends, a polyfunctional isocyanate curing agent including at least an aliphatic polyfunctional isocyanate compound, and an aliphatic compound having a plurality of functional groups in one molecule capable of reacting with an isocyanate group.

2. The power storage device according to claim 1, wherein an equivalent ratio [NCO] / [OH+COOH], which is a ratio of the number of moles of isocyanate groups of the polyfunctional isocyanate curing agent to the sum of the number of moles of the hydroxyl groups and the number of moles of the carboxyl groups, is 0.5 to 5.

3. 3. The electricity storage device according to claim 1, wherein the aliphatic polyfunctional isocyanate compound is at least one aliphatic polyfunctional isocyanate compound selected from the group consisting of an adduct of trimethylolpropane and an aliphatic diisocyanate compound, and an adduct of pentaerythritol and an aliphatic diisocyanate compound.

4. 4. The electricity storage device according to claim 1, wherein the protective layer further contains solid fine particles.

5. 5. The electricity storage device according to claim 1, further comprising a colored layer disposed on the exterior member.

6. 6. The electricity storage device according to claim 1, wherein the number average molecular weight is 11,200 to 49,000.

7. 7. The electricity storage device according to claim 1, wherein the gloss value of the surface (outer surface) of the protective layer is 30% or less.

8. The power storage device according to any one of claims 1 to 7, characterized in that the power storage device main body is at least one selected from the group consisting of a lithium secondary battery such as a lithium ion battery or a lithium polymer battery, a lithium ion capacitor, an electric double layer capacitor, and an all-solid-state battery.

9. A method for manufacturing an electricity storage device including an exterior member and an electricity storage device main body, comprising: the exterior member includes a base layer made of a heat-resistant resin, a sealant layer as an inner layer, and a metal foil layer disposed between the base layer and the sealant layer, The method for producing an electricity storage device includes a step of obtaining an exterior member having a protective layer on a surface of the base material layer opposite to the metal foil layer, the protective layer containing 40 mass% or more of a polyester resin formed from a polyester polyol having a number average molecular weight of 5,000 to 50,000 and having a hydroxyl group or a carboxyl group, independently at least at both ends, a polyfunctional isocyanate curing agent including at least an aliphatic polyfunctional isocyanate compound, and an aliphatic compound having a plurality of functional groups in one molecule that can react with an isocyanate group.

10. a step of forming the exterior member to obtain an exterior case having a recessed accommodation portion; accommodating the power storage device main body in the accommodation recess; placing the unformed, planar exterior member on the power storage device main body; a step of heat-sealing a peripheral portion of the planar exterior member and a peripheral portion of the exterior case; The method for manufacturing an electricity storage device according to claim 9 , further comprising:

Citation Information

Patent Citations

  • Laminated material for secondary battery container and secondary battery container

    JP2003288865A

  • Coating for metal package and metal package using the same

    JP2004359759A

  • Packaging material for electrochemical cell

    JP2011054563A

  • Polyurethane adhesive for a battery packaging material, battery packaging material, battery container, and battery

    JP2014091770A

  • Packaging material for batteries, container for batteries and battery

    JP2015082354A